A novel coumarin-based fluorescence chemosensor containing l-histidine for aluminium(iii) ions in aqueous solution1. Issue 15 (7th August 2015) - Yan, Li-Qiang; Ma, Yun; Cui, Mei-Fang; Qi, Zheng-Jian
<x xml:space="preserve">Abstract</x> A highly selective "Turn-on" fluorescence chemosensor containing l-histidine for aluminium(iii) ions was readily synthesized and investigated in pure aqueous solution.